Filter Hybrid Double-Tuned dan High-Pass untuk Mitigasi Harmonisa pada Sistem HVAC Inverter - Malik, Mochamad Irlan; Hamdani, Yuda Muhammad; Nurdiansyah, Rian; Faridah, Linda; Nurmela (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2025)
Inverter-based Heating, Ventilation, and Air Conditioning (HVAC) systems are increasingly utilized in industrial settings for their superior energy efficiency and controllability. Despite these advantages, nonlinear switching in inverters generates significant harmonic distortion, particularly at lower-order frequencies such as the 3rd and 5th, which can compromise power quality, reduce system lifespan, and lead to non-compliance with regulatory standards. This study proposes a hybrid passive filter solution—combining a Double Tuned Filter (DTF) and a High Pass Filter (HPF)—to mitigate harmonic distortion in an industrial HVAC system. Field data collected using a Power Quality Analyzer (PQA) revealed a 3rd-order Individual Harmonic Distortion of Current (IHDi) of 12.9%, far exceeding the 4.0% threshold specified in IEEE 519:2022. The hybrid filter was analytically designed and validated through MATLAB/Simulink simulation. Post-simulation results demonstrated effective mitigation of Total Harmonic Distortion (THD) to 3.45%, with the 3rd-order IHDi mitigated to 3.42%, achieving full compliance with IEEE 519:2022. Furthermore, the hybrid filter preserved voltage waveform quality and suppressed high-order harmonics without incurring additional energy losses or resonance issues. The combination of DTF and HPF offers wide-spectrum harmonic mitigation and enhanced power system stability. This solution is well-suited for high-load, scalable infrastructures aligned with Industry 4.0 requirements. The study concludes that passive hybrid filters are a reliable and cost-effective strategy for harmonic suppression, and future work should explore real-time adaptive control and hybrid active-passive configurations for enhanced dynamic performance